Seeing red: flushing out instigators of niacin-associated skin toxicity - Dunbar, Richard L. (American Society for Clinical Investigation, 2010)
The use of niacin to improve plasma lipid levels and reduce risk of myocardial infarction is limited by noxious skin effects that result from stimulation of G protein–coupled receptor 109A (GPR109A) in skin immune cells. Niacin causes vasodilation, manifest as rubor (redness) of the head and neck, providing a visible sign associated with other, more bothersome skin complaints. The working theory is that niacin provokes Langerhans cells to produce prostaglandin D(2) (PGD(2)), stimulating vascular DP1 receptors to cause vasodilation. In this issue of the JCI, Hanson and colleagues raise a serious challenge to this paradigm in showing that the major player in vasodilation is the keratinocyte, which produces PGE(2), stimulating EP(2/4) receptors, shifting the role of the Langerhans/PGD(2)/DP(1) pathway to that of an accomplice. They also show that the antipsoriasis drug monomethyl fumarate, itself a GPR109A agonist, provokes vasodilation through the same cells. These efforts bring us one step closer to solving a key limitation of an important cardioprotective drug and reveal that the skin response to niacin is much more complicated than previously thought.